PENERAPAN RECURRENT NEURAL NETWORK UNTUK SISTEM PERINGKASAN DAN PENERJEMAHAN TEKS BERITA BAHASA INGGRIS KE BAHASA INDONESIA - Adika Rajendra Haris (2023)
The development of the internet has allowed people to read different kinds of news from various parts of the globe. Of course, because the number of news keeps increasing, more news articles are becoming too long in length to read and written in languages different from Indonesian making the readers unable to grasp the meaning of the news. This research will apply Recurrent Neural Network (RNN) to summarize and translate English news to the Indonesian language. The expected result is two RNN model in which one will summarize the text in English and one will translate said text to Indonesian.